Habent sua fata fragmenta"" : Festschrift in Honour of Mauro Perani Offered by Friends and Colleagues, European Genizah Texts and Studies, Volume 7 - Abate, Emma,; Campanini, Saverio,; Olszowy-Schlanger, Judith,; Veltri, Giuseppe, (Early Modern History and Modern History E-Books Online, Collection 2025., 2025)
This volume, dedicated to celebrating Professor Mauro Perani's career, encompasses a collection of original and groundbreaking essays on Hebrew and Jewish manuscripts, from late antiquity onwards, by international scholars and specialists of Hebrew palaeography, philology and Jewish history. The first section deals with research on documents, letters and literary sources shading new light on forgotten aspects of Medieval and Early Modern Jewish history. The second part introduces to recent discoveries and analysis of Hebrew fragments found reused as bindings and covers of other books in European libraries and archives.